G392(P) Preparing for paediatric intensive care – the development of a paediatric intensive care unit simulation induction course for trainee doctors. (27th April 2015) - Blakemore, L; Lumsden, J
Abstract : Aims: On our paediatric intensive care unit (PICU) doctors induction traditionally consisted of a series of lectures and small group work. In order to make introduction more interactive and enhance learning, we decided to set up a one day simulation based induction course. Methods: Learning needs were identified from informal survey of current trainees and PICU consultants. Four simulation scenarios were designed to encompass the learning objectives established from the learning needs survey and key competencies needed for PICU. Scenarios involved patients transferred to PICU for stabilisation, or deteriorating patients on the unit. 30 min simulations and were followed by 1 h debrief and tutorial. Tutorials focused on medical management and practicalities such how to set up a ventilator or give inotropes. Simulations ran with 2–3 trainees and 2 PICU nurses per scenario, and were set up in a cubicle with standard equipment, using high fidelity manikins. Due to anticipated inexperience, trainees were offered "time out" and "ask the audience" options during the scenarios to enable them to draw on the knowledge of their peers. Results: 10 trainees completed the simulated induction course. When asked to use a 5 point likert scale, 90–100% of trainees either agreed or strongly agreed to all but one of the 9 statements related to the course meeting learning objectives and knowledge needs. High frequency oscillation was the single area that was identified by trainees as not being covered in desired depth. Free text feedback was overall very positive. Suggestions for improvement would be to provide a specific ventilation workshop to enable this subject to be covered in greater depth, plus a written handout to supplement the day. We are waiting to see how the induction evaluates in the GMC survey, compared to traditional induction. Conclusion: We ran a pilot PICU simulation induction which was well received by trainees, and met all but one learning objective. The course could be easily adapted to address this objective and could be tried in other Paediatric Intensive Care Units.